Heterogeneity of the rearing environment enhances diversity of microbial communities in intensive farming - Ashrafi, Roghaieh; Sundberg, Lotta-Riina; Hyvärinen, Pekka; Karvonen, Anssi (BioMed Central, 2024)
Heterogeneity of the rearing environment in farmed animals can improve welfare and stocking success by enhancing natural behaviours, reducing stress, and decreasing pathogen occurrence. Although microbial diversity is often associated with well-being, their direct and indirect effects on health of farmed animals remain underexplored. We examined the impact of structural heterogeneity of aquaculture tanks on microbial communities in tank biofilm and fish gut microbiome. Enrichment (stones and shelters) significantly promoted microbial diversity and community homogeneity in tank biofilm. However, diversity of gut microbiome did not depend on rearing treatment or microbial composition of the environment. Fish in enriched tanks exhibited greater compositional variation in gut microbiome than those in standard tanks. Tanks without enrichments had higher occurrence of potentially pathogenic bacterial families (Corynebacteriaceae and Staphylococcaceae), while enriched tanks had more beneficial gut microbes (Lactobacillus). Microbial diversity in tank biofilm was negatively associated with fish mortality during a natural epidemic of Flavobacterium columnare, suggesting a protective effect of diverse microbial communities. These findings support environmental enrichment in mitigating disease outbreaks through enhanced microbial diversity, providing important implications for disease control and sustainable health management in aquaculture.
Keywords: enriched rearing; microbiome; Atlantic salmon; intensive farming; biofilms; microbial composition